2021
DOI: 10.1038/s41598-021-01072-1
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen shades of clay: distinct microbial community profiles obtained from bentonite samples by cultivation and direct nucleic acid extraction

Abstract: Characterizing the microbiology of swelling bentonite clays can help predict the long-term behaviour of deep geological repositories (DGRs), which are proposed as a solution for the management of used nuclear fuel worldwide. Such swelling clays represent an important component of several proposed engineered barrier system designs and, although cultivation-based assessments of bentonite clay are routinely conducted, direct nucleic acid detection from these materials has been difficult due to technical challenge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 60 publications
3
14
0
Order By: Relevance
“…The microbiome obtained from dry clay materials may not represent the full diversity of the community due to the inability to detect low-abundance species. This is evidenced when comparing the microbial diversity of dry clay and that of the same clay placed in water with an electron donor/acceptor ( Vachon et al, 2021 ). Therefore, it is not a trivial exercise to pinpoint the origin of the microbial community identified in the 4 reactors.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiome obtained from dry clay materials may not represent the full diversity of the community due to the inability to detect low-abundance species. This is evidenced when comparing the microbial diversity of dry clay and that of the same clay placed in water with an electron donor/acceptor ( Vachon et al, 2021 ). Therefore, it is not a trivial exercise to pinpoint the origin of the microbial community identified in the 4 reactors.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] These changes in environmental conditions will also influence the activity of the microbes that are naturally found in bentonite clay, including sulfate‐reducing bacteria (SRB). [ 9 ] Upon emplacement, the bentonite clay's water activity will be low, suppressing microbial activity. The effects of irradiation and increased temperature from the decaying fuel inside the UFC have also been shown to eliminate spore‐forming bacteria below the detection limits of culturing.…”
Section: Introductionmentioning
confidence: 99%
“…Due to bentonite's inhospitable physical and chemical properties, the number of culturable microbes in bentonite is very low, ranging from 10 2 to 10 3 colony‐forming units per gram. [ 9 ] The low metabolic activity in bentonite clay is attributed partly to the high swelling pressure, low water activity, and small pore size. Previous studies determined that the number of metabolically active microbes decreases at higher bentonite dry densities.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfate-reducing bacteria (SRB) are of specific interest due to their production of hydrogen sulfide gas (H 2 S), which has potential for UFC metal corrosion. Although previous studies have explored microbial communities present in as-received, uncompacted bentonite clay and lab-scale pressure vessels ( 3 8 ), few SRB are detected and this may be a result of bentonite-associated inhibition. In particular, highly compacted bentonite can inhibit microbial growth when exceeding 1.6 g/cm 3 dry density, which corresponds to water activity below 0.96 and swelling pressures exceeding 2 MPa ( 9 ), and it was shown that swelling bentonites decrease sulfide production by SRB ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study featuring ancient analog samples reported low cultivable heterotroph and SRB associated with a bentonite deposit that was formed ~10 million years ago and sequencing of SRB cultures revealed that the taxon present was affiliated with the genus Desulfosporosinus ( 7 ). An analysis of dry, uncompacted bentonite clay samples showed that cultivation-based approaches were consistently associated with phylogenetically similar SRB, aerobic heterotrophs, and fermenters ( 8 ). Dominant nucleic acid sequences extracted from these dry clay samples did not correspond with the bacteria that were enriched or isolated in culture, and relatively few core taxa (e.g., Streptomyces , Micrococcaceae , Bacillus , and Desulfosporosinus ) were shared among cultivation and direct nucleic acid analysis profiles ( 8 ).…”
Section: Introductionmentioning
confidence: 99%